Analisis Laporan Keuangan Dikaitkan Dengan Kinerja Pemerintah Daerah (Studi Kasus pada Pemerintah Daerah Kota Bandar Lampung) - Hassan Basrie; Yashinta Arly; Riswan RISWAN (Universitas Bandar Lampung (UBL), 2012)
The purpose of this research is to analyze the financial statements associated with the performance of local government in the city of Bandar Lampung. The demands of public sector accountability towards the realization of good governance good governance in Indonesia is increasing. This demand is reasonable, because some research suggests that the onset of the economic crisis in Indonesia was caused by poor management (bad governance) and bad bureaucracy. Good governance is a management organization of development that is in line with the principle of democracy, the avoidance of any allocation of investment funds, the prevention of corruption both in administrative and political or the realization of good governance required competent human resources and in order to put together a quality financial statements so that the performance of local government in the city of Bandar Lampung can be the maximum. So the problem is taken is how financial statement analysis associated with the performance of local government in the city of Bandar Lampung.